Penerapan Self Hipnosis untuk Menurunkan Kecemasan dan Meningkatkan Imunitas Penderita COVID-19 di BAN Diklat Kota Lubuklinggau - Zuraidah Zuraidah; Nadi Aprilyadi; Indah Dewi Ridawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
The number of sufferers and deaths due to the COVID-19 virus is increasing both in Indonesia and various countries in the world. The COVID-19 virus can attack the body's immune system. If a person with COVID-19 experiences anxiety and their immune system decreases, the condition of the patient with COVID-19 is at risk of getting worse and even death. One of the non-pharmacological treatments to reduce anxiety and increase body immunity is hypnotherapy. This community service is partnered with BAN Diklat Lubuklinggau City and aims to train and provide non-pharmacological treatment for COVID-19 sufferers in Lubuklinggau City. The activity will be held on August 24, 2020 at 08:00 WIB - 13:00 WIB. The form of activity is training three times for 20-30 minutes. This self-hypnosis training was attended by 25 people with COVID-19. The results of this activity were the implementation of self-hypnosis training to increase participants' immunity, participants' skills in self-hypnosis increased by 76% and as many as 60% of Covid-19 sufferers at BAN Diklat Lubuklinggau City no longer felt anxious. Efforts to reduce anxiety and increase body immunity are expected to be implemented and continued